PENGARUH PROGRAM X-SCHOOL OLEH XK-WAVERS TERHADAP PEMBENTUKAN KESADARAN BERAGAMA ISLAM BAGI PECINTA KOREA - Rafidatikna, Afifah; Amrullah, Abdul Malik Karim (Muta'allim: Jurnal Pendidikan Agama Islam, 2022)
This study analyzes the X-School Program on the formation of religious awareness for Korean lovers. The problem raised in this study is that many young Indonesians, the majority of whom are Muslims, actually show their alignment with Korean culture. Something that is actually entertainment is starting to be used as a new mecca in living life even though there are many teachings from Korean culture which in practice are actually contrary to Islamic teachings. This research utilizes a quantitative research approach with the type of ex post facto research. This study aims to determine the X-School program implemented by XK-Wavers, to explain the condition of Islamic awareness of Korean lovers who follow the X-School program, and to determine the effect of the X-School program on the formation of Muslim awareness of Korean lovers who follow the X-School program. -School. The findings in this study indicate that the X-School Program conducted by XK-Wavers is in the good category, the religious awareness of the alumni of the X-School program is categorized as good, and the X-School Program has an influence of 42.1% on the formation of Islamic awareness for alumni X-School program. Abstrak Penelitian ini menganalisis Program X-School tehadap pembentukan kesadaran beragama bagi pecinta Korea. Masalah yang diangkat dalam penelitian ini adalah karena banyaknya generasi muda Indonesia yang mayoritas adalah muslim justru memperlihatkan keberpihakannya pada budaya Korea. Sesuatu yang sejatinya hiburan mulai dijadikan sebagai kiblat baru dalam menjalani kehidupan meskipun terdapat banyak ajaran dari budaya Korea yang dalam praktiknya justru bertolak belakang dengan ajaran Islam. Penelitian ini memanfaatkan pendekatan penelitian kuantitatif dengan jenis penelitian ex post facto. Penelitian ini bertujuan untuk mengetahui program X-School yang dilaksanakan oleh XK-Wavers, untuk menjelaskan kondisi kesadaran beragama Islam pecinta Korea yang mengikuti program X-School, dan untuk mengetahui pengaruh program X-School terhadap pembentukan kesadaran beragama Islam pecinta korea yang mengikuti program X-School. Temuan pada penelitian ini menunjukkan bahwa Program X-School yang dilakukan oleh XK-Wavers masuk dalam kategori baik, kesadaran beragama alumni program X-School dikategorikan baik, dan Program X-School memberikan pengaruh sebesar 42,1% terhadap pembentukan kesadaran beragama Islam bagi alumni program X-School.